Yammer Collaborate, Connect, and Share - Waghmare, Charles (Apress, 2018)
Build a successful Yammer implementation, make your workplace social and collaborative, create a culture of sharing, form expert communities and generate innovative solutions. Besides, this book will help to enhance your collaboration your suppliers, partners, and clients. The author starts by giving an introduction to social collaborations and successful implementations of Yammer. Along the way, he explains the art of community management in Yammer using his hands-on experience of building communities. He then explains methods to keep a Yammer network engaged followed by a description of running a campaign on Yammer. The second part of Yammer begins with ways you can engage entire organizations, including executives, on Yammer along with methods to measure the success of a Yammer network. You'll see how to get to grips with integrating Yammer with an existing platform and how to collaborate with customers, suppliers, and partners using Yammer. Finally, you'll learn various innovative techniques of communication using Yammer and explore the author's vision of the next-generation Yammer platform After reading this book you will understand how to make successful Yammer implementations, engage communities on Yammer, and accomplish business goals using Yammer. You will: Master the art of community management Make your organization digital by implementation and integration of Yammer Break silos and create a collaborative workforce Keep Yammer groups live and full of participation Improve collaboration between suppliers, partners, and clients Measure success of your Yammer network Increase employee engagement on Yammer .